Comparison of cytotoxic and anti-platelet activities of polyphenolic extracts from Arnica montana flowers and Juglans regia husks. (27th March 2014) - Rywaniak, Joanna; Luzak, Boguslawa; Podsedek, Anna; Dudzinska, Dominika; Rozalski, Marcin; Watala, Cezary
Abstract: Polyphenolic compounds of plant origin are well known to be beneficial to human health: they exert protective effects on haemostasis and have a particular influence on blood platelets. However, the anti-platelet properties of polyphenolic compounds observed so far have not been weighed against their potential cytotoxic action against platelets. The aim of this study was to demonstrate that anti-platelet and cytotoxic effects on blood platelets may interfere and therefore, may often lead to confusion when evaluating the properties of plant extracts or other agents towards blood platelets. The anti-platelet and cytotoxic in vitro effects of plant extracts obtained from the husks of walnuts ( J. regia ) and flowers of arnica ( A. montana ) on platelet reactivity and viability were examined. Platelet function was assessed using standard methods (flow cytometry: P-selectin expression, activation of GPIIbIIIa complex, vasodilator-stimulated phosphoprotein, VASP index; turbidimetric and impedance aggregometry) and newly set assays (flow cytometric monitoring of platelet cytotoxicity). The results reveal that none of the studied plant extracts demonstrated cytotoxicity towards blood platelets. The phenolic acid-rich extract of A. montana (7.5 and 15 µg/ml) significantly reduced the ADP-induced aggregation in both whole blood and PRP, and decreased the platelet reactivity index (PRI; VASP phosphorylation) in whole blood, while showing excellent antioxidant capacity. The extract of J. regia husks significantly reduced ADP-induced platelet aggregation in whole blood when applied at 7.5 µg/ml, and only slightly decreased the PRI at 15 µg/ml. Both examined extracts suppressed platelet hyper-reactivity, and such influence did not interfere with cytotoxic effects of the extracts. Thus, its high polyphenol content, excellent antioxidant capacity and distinct anti-platelet properties, in combination with its lack of toxicity, make the extract of A. montana flowers a possible candidate as an anti-platelet agent or a compounding diet supplement.